MARKETING PERFORMANCE THROUGH COMPETITIVE ADVANTAGE BASED ON INNOVATION IN EDUCATIONAL SERVICE AT PRIVATE POLYTECHNICS IN INDONESIA - Jajang Burhanudin; Dwi Kartini; Sucherly Sucherly; Rita Komaladewi (Journal of International Conference Proceedings (JICP), 2019)
Today, private polytechnics are required to innovate towards competitive advantage and superior performance in the higher education sector. However, in reality the accreditation is low, there is a lack of intellectual property rights and patents, many students drop out and have a long working period for graduates. Using a survey of all private polytechnics in West Java and Banten Province in Indonesia 30 institutions with 876 respondents from faculty members and students assigned randomly. The results of the study show that educational service innovation has an effect on competitive advantage and marketing performance. Competitive advantage also affects marketing performance.